2013
DOI: 10.1007/s10964-013-0080-9
|View full text |Cite
|
Sign up to set email alerts
|

Does Mother Know Best? Adolescent and Mother Reports of Impulsivity and Subsequent Delinquency

Abstract: Although impulsivity is one of the strongest psychological predictors of crime, it is unclear how well impulsivity, measured at a specific moment in adolescence, predicts criminal behavior months or years into the future. The present study investigated how far into the future self-reports and parents' reports of a youth's impulsivity predicted whether he engaged in illegal behavior, whether one reporter's assessment was more predictive than the other's, and whether there is value in obtaining multiple reports.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…12-14,30-33 In the Pathways to Desistance study of 701 adjudicated adolescents, Bechtold and colleagues (2013) found that adolescent impulsivity was associated with criminal behaviors throughout late adolescence and early adulthood. 14 Moreover, impulsivity was identified as a significant predictor for violent crime such as physical fighting, using a weapon, hurting another person, armed robbery, and intimate partner violence. 34 Given the critical role impulsivity plays in involvement in crime, it is not surprising to note that most risk assessment measures for criminal offending are designed to measure impulsivity more than any other constructs.…”
Section: Introductionmentioning
confidence: 99%
“…12-14,30-33 In the Pathways to Desistance study of 701 adjudicated adolescents, Bechtold and colleagues (2013) found that adolescent impulsivity was associated with criminal behaviors throughout late adolescence and early adulthood. 14 Moreover, impulsivity was identified as a significant predictor for violent crime such as physical fighting, using a weapon, hurting another person, armed robbery, and intimate partner violence. 34 Given the critical role impulsivity plays in involvement in crime, it is not surprising to note that most risk assessment measures for criminal offending are designed to measure impulsivity more than any other constructs.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with a breadth of previous evidence showing elevated sensation seeking among antisocial youth (Byck et al, 2015; Mann, Kretsch, Tackett, Harden, & Tucker-Drob, 2015; Newcomb & McGee, 1991; Sijtsema et al, 2010; Zuckerman, 2007). Previous research has also demonstrated a positive relationship between impulsivity and delinquency (Bechtold, Cavanagh, Shulman, & Cauffman, 2014; Cooper et al, 2003; Frick & Viding, 2009; Giannotta & Rydell, 2015; Moffitt, 1993; Snowden & Gray, 2011; Vitacco & Rogers, 2001). Moreover, both impulsivity and sensation seeking have been implicated in the development of related externalizing behaviors in adolescence, including alcohol and substance use (Dick et al, 2010; Elkins, King, McGue, & Iacono, 2006; Hittner & Swickert, 2006; Littlefield & Sher, 2010; Littlefield, Sher, & Steinley, 2010).…”
Section: Sensation Seeking and Impulsivity Predict Adolescent Asbmentioning
confidence: 92%
“…Parents can provide a view into their children's lives that others cannot. Bechtold and others () found mothers' insights into the impulsivity of their teens quite useful in predicting future arrests, and Rosenberg and others () noted that parents offered insights about their young children useful to occupational therapists.…”
Section: Methodsmentioning
confidence: 99%